Controlled Synthesis of Octahedral Platinum‐Based Mesocrystals by Oriented Aggregation. Issue 28 (27th March 2017) - Zhong, Ping; Liu, Hongpo; Zhang, Jie; Yin, Yadong; Gao, Chuanbo
Abstract: Designed synthesis of noble metal mesocrystals is of great significance for a variety of applications. Here, the synthesis of octahedral Pt‐Ag alloy mesocrystals with precisely controlled morphology, size, and exposing facets, formed by oriented aggregation of their crystallites, is reported. The critical role of bromide was revealed in regulating the overall octahedral morphology of the Pt–Ag mesocrystals, by bridging the interactions between the capping agent and the Ag‐modified Pt crystallites. The size of the mesocrystals was precisely controlled in a broad range by tuning the number of the seeds, all retaining their octahedral morphology. Based on this understanding, octahedral Pt–Ag mesocrystals exposing {1 1 1} facets have been obtained in a highly controllable and reproducible manner. This material showed excellent electrocatalytic activity and stability in oxygen reduction reactions (ORR). It is hoped that the current synthesis provides new insights that pave the way to diverse faceted nanocrystals/mesocrystals for high‐performance catalytic and many other applications. Abstract : Platinum : Octahedral Pt–Ag alloy mesocrystals with precisely controlled morphology, size, and exposing facets have been synthesized by seed‐mediated oriented aggregation. These mesocrystals demonstrate excellent electrocatalytic activity and stability due to their exceptional facet‐selectivity and self‐supported nanostructure.